Design of Detainee Deportation Tracking System at Jakarta Immigration Detention Center - Duantara, Haryadi; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Yayasan Bina Internusa Mabarindo, 2023)
The Jakarta Immigration Detention Center is an immigration technical implementation unit engaged in the field of immigration, which includes prosecution, isolation, and deportation or repatriation. Companies that have another name, namely Rudenim, have problems in the deportation reporting system. The author has conducted observational research and conducted interviews with related parties, and found several problems in terms of data collection on detainees and deportation of detainees. From the results of this study the authors have a suggestion to immediately have a Web-Based Deportation Tracking System at the Jakarta Immigration Detention Center. Where the system can help, even improve the operation of the deportation report system quickly and accurately.